Jejak Parsi dalam Sejarah Kebudayaan dan Sastra Melayu - Hadi W.M., Abdul Hadi W.M. (Lajnah Pentashihan Mushaf Al-Qur'an, 2010)
This paper examines the influence of Persia in the history of Malay culture and literature. Persian influence appears in prayers, religious ceremonies and the tendency towards Sufi ideas. It is also found in Malay vocabulary, types of writing, traditional literary romances known as hikayat, poetry and historical texts. Further influence appears in Malay cultural values, canon law and religious treatises which are commonly also regarded as literary works. This influence is not coincidental but the result of historical factors which cannot be ignored. Persian religious scholars, intellectuals and cogniscenti played an important role in the spread of Islam and its intellectual traditions. This influence can be seen in works such as Taj al-Salitan, Hikayat Amir Hamzah, Hikayat Muhammad Ali HanafiyanÃ‚Â and Hikayat Burung Pingai.